Fiqh Muamalah Analysis of People's Business Credit (KUR) Products with Rahn Contract at Sharia Pawnshop Kusumanegara Branch Yogyakarta - Arief, Suyoto; Aziz, Muhammad Abdul; Hasbi, Noval; Maulana, Ahmad Ageng (TAWAZUN: Journal of Sharia Economic Law, 2025)
Sharia pawnshop is a financial institution that operates based on sharia principles in the Islamic financial system. Sharia pawnshop provides financial services in accordance with Islamic principles to the public, which includes financing and collateral services in a halal manner in accordance with Islamic law. This provides an alternative to individuals and businesses who want to access financing or pledge their assets without violating religious principles. The aim of this research is to find out the mechanism of the People's Business Credit (KUR) Product at the Kusumanegara Branch of Yogyakarta sharia pawnshop and to find out the Fiqh Muamalah Analysis Regarding People's Business Credit (KUR) Products with Rahn Contracts at the Kusumanegara Branch Yogyakarta of Sharia Pawnshops. This research uses descriptive qualitative research methods, the data sources used are primary and secondary data. and this research is included in field research with observation, interviews and documentation as techniques for data collection. Based on the results of the discussion from this research, it can be seen from Fiqh Muamalah that the practice of rahn contracts on People's Business Credit (KUR) products at the Kusumanegara sharia pawnshop is not in accordance with Islamic law because there is no Al-Marhun submitted by customers to the sharia pawnshop.